RESULTS OF THE PYRETHROID RESISTANCE MONITORING PROGRAM OF Hellothis virescens IN COTTON - Manejo de Plaguicidas, Grupo Integrado de (Revista Colombiana de Entomología, 1991)
One of GIMP’s (Grupo integrado de Manejo de Plaguicidas) objectives is to monitor pyrethroid-resistance of Hellothis virescens in Colombia. With this program, changes in the susceptibility of the insect population are procured, early signs of control failures are detected and the efficacy of a management strategy of the insecticidal group involved in the resistance problem can be evaluated. Employing both topical application and dip tests, a total of 131 tests with samples of H. virescens from 60 collection sites the in-country, were carried out to determine its susceptibility to cypermethrin. For topical application, a discriminatory dose of 1.0 pg/g of the larva was used, with which theoretically 100% of the individuals of a susceptible population is killed. In the dip test, the doses of 10 and 100 ppm were tested, and occasionally the whole range of 0.1 to 1000 ppm. The results obtained show the highest tolerance of H. virescens to cypermethrin during 1988-89 in the coastal cotton growing area in Magangué (Bol.), wherewith the di discriminatory dose only a 68% mortality was obtained; this was followed by Aguachica (Cesar) 70%, Bosconia (Cesar) 72% and Cereté (Cord.) with 85% mortality respectively. In the interior cotton-growing area, the region with the highest tolerance was Chicoral-Espinal (Tol) with 73% mortality, while in the Cauca Valley the mortality fluctuated between 84% for El Vínculo (Buga) and 100% for La Rioja (Roldanillo). A similar tendency of tolerance was found using the dip test, where the LC50 varied from 0.18 ppm for Palmaseca at Palmira (Valle) to 150 ppm for San Pelayo (Córdoba). It was also possible to prove that as pyrethroids are sprayed during one season, Heliothis tolerance to them increases, while when not used, susceptibility increases. The general conclusion reached was that in all cotton-growing areas of Colombia, pyrethroids should be sprayed against H. virescens with caution and in a restricted way, to avoid an increase of the resistance problem to this group of insecticides.